Examining the Role of Religion in Radicalization to Violent Islamist Extremism - Aly, Anne; Striegher, Jason (Routledge Taylor and Francis, 2012)
In this article, the authors apply the four-phase radicalization model proposed by Silber and Bhatt1 to a case study of Australia’s first convicted terrorist, Jack Roche, based on communication with Roche after his incarceration and on a qualitative analysis of his trial. In doing so, they examine the validity of the four-phase model to a case of “home grown” terrorism and dissect the role of religion in the radicalization process. To conclude, the authors find that religion plays a far lesser role in radicalization toward violent extremism than the policy response contends and this has implications for counterterrorism programs that aim to address the drivers of violent extremism.